2018
DOI: 10.17159/0379-4350/2018/v71a7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Electrochemical Study on the Control of Mild Steel Corrosion in Hydrochloric Acid Solution with Bitter Kola Leaf Extract as Inhibitor

Abstract: Response surface methodology was applied to predict the optimum control of mild steel corrosion in acid medium with bitter kola leaf extract as inhibitor. The experiment was carried out to investigate the mutual interactions between the considered independent variables and the expected responses. Thermometric, gravimetric, potentiodynamics polarization and electrochemical impedance spectroscopy were used in the corrosion inhibition study. As a supplementary technique, infrared spectroscopy was used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Therefore, inhibitors with high dipole moment form strong dipole-dipole interactions with the metal, ensuring a strong adsorption on the surface of the metal and leading to higher inhibition efficiency. It was observed that the dipole moment value for Levaquin shown in Table 5 correlates with the experimental results reported elsewhere [32][33][34][35].…”
Section: Dipole Momentsupporting
confidence: 88%
“…Therefore, inhibitors with high dipole moment form strong dipole-dipole interactions with the metal, ensuring a strong adsorption on the surface of the metal and leading to higher inhibition efficiency. It was observed that the dipole moment value for Levaquin shown in Table 5 correlates with the experimental results reported elsewhere [32][33][34][35].…”
Section: Dipole Momentsupporting
confidence: 88%
“…This EEC is composed from few elements due to the solution resistance (Rs), charge-transfer resistance of the interfacial corrosion reaction (Rct) and the constant phase element (CPE) due to double-layer impedance. Impedance of CPE (ZCPE) is defined as [19,20,[32][33][34]:…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Weight loss method was performed at temperatures of 303 K, 318 K and 333 K, respectively. As previously expressed 10,16 the variation in the initial and final weight was studied for unprotected and protected test solution. At the end of corrosion study the coupons were removed, dipped in acetone, cleaned and finally re-weighed.…”
Section: Weight Loss Methodsmentioning
confidence: 99%
“…Further observation revealed that the activation energies increase as the concentration of SE molecules increases due to the spontaneous accumulation of SE molecules on steel surface which led to a considerable surface coverage and the film layer is seen to be higher than the destruction of the steel surface. 10…”
Section: Adsorption / Thermodynamics Studymentioning
confidence: 99%
See 1 more Smart Citation